A novel method of 3D printing locating guide for abutment screw removal in cement-retained implant-supported prostheses - Jiali Yu; Yanbin Chen; Xiangzhen Liu; Rafiqul Islam; Mohammad Khursheed Alam (Elsevier, 2022)
Background/purpose: Cement-retained restorations have the advantages of passive fit, less complexity of clinical and laboratory methods, cost, esthetics, and dimensional stability over screw-retained restorations, especially in multiple abutment implant-supported prostheses. A common and difficult technical problem with cement-retained implant prostheses is abutment screw loosening. Three-dimensional (3D) printing is a technology that has been rapidly developed and has become widely accepted in dentistry. The aim of this study was to establish a novel method of using 3D implant planning guide to locate the abutment screw in cement-retained implant prosthesis. Materials and methods: Six standard gypsum complete denture models were used to locate the abutment screw. An implant analog (4.5 mm in diameter and 12 mm in length) was placed in the drilling hole (5 mm in diameter and 14 mm in depth). After scanning with a 3D scanner, the 3D printing software was used to design the abutment screw location guide, which was printed by a resin-based 3D printer. Results: A total of 30 abutment screws were located and removed using the guide. The locating guide's actual diameter was 2.4 mm. The drilling point was accurate and precise, and no excessive loss of the abutment was noticed. Conclusion: The guide would help the dentist in locating the abutment screw access channel, resulting in a more precise and accurate drilling point. The guide for locating the abutment screw enhances the accuracy of screw channel access and reduces damage to the crown and abutment.